Implementasi Metodologi Extreme Programming Dalam Perancangan Website Sistem Informasi Posyandu Melati Di Desa Talaga - Alfatira, Maulana Rizki; Rahmawati, Diah; Rismaningsih, Febri (Jutis (Jurnal Teknik Informatika), 2023)
Posyandu Melati is an activity that is routinely carried out every month to monitor the health of pregnant women and toddlers in Talaga Village. With posyandu activities, cadres need to announce posyandu activities through mosque and prayer room speakers, causing information not to be received evenly throughout society. In addition, the management of participant data is also still done manually by recording it on sheets of paper. Because of this, an information system design was created that aims to facilitate activities at the Melati Posyandu. For this reason, an information system is designed using the Extreme Programming method. This method is used to increase the adaptability and flexibility of information systems because this method is able to adapt to changing requirements. Based on the application that has been tested, it can assist cadres in carrying out activities at Posyandu. The information system has features in sending posyandu schedules better and conveying information more evenly to the public, and the management of participant data will become more organized with this information system. Thus the design can run more smoothly and provide optimal benefits for the people in Talaga Village